Effect of aspect ratios on longitudinal and lateral motions of unmanned aerial vehicle - Abdullah, Ermira Junita (Federation of Engineering Institutions of Islamic Countries, 2006)
The study of wing with varying aspect ratio is critical in the development of the morphing wing for Unmanned Aerial Vehicle (UAV). A morphing wing permits a change in the camber, aspect ratio, wing twist and wing sweep while simultaneously supporting structural wing loads. UAV with this wing design will be able to carry out multiple objectives mission. This paper investigates the effect of aspect ratio on the stability of the longitudinal and lateral motions of UAV. The poles of the motions are calculated and root locus for the motions are plotted to validate that the variable aspect ratio (VAR) wings sustain stability during symmetric changes in wing span. Preliminary study on the stability of a generic UAV shows that it remains stable for values of aspect ratio from 3 to 10.